Evaluation of Flood Resilience in Shanghai Based on Extension Cloud Model - LI Chen; DUAN Yonghui (Renmin Zhujiang)
This study aims to construct a flood resilience evaluation index system for Shanghai based on the DPSIR model, revealing the dynamic characteristics of urban flood resilience through quantitative assessments and providing a scientific basis for enhancing the urban flood prevention capabilities and dealing with flood disasters. Based on the DPSIR model, the evaluation system encompassed a total of 22 indicators across five dimensions: drivers, pressure, state, impact, and response. The analytic hierarchy process (AHP) was employed to calculate the weights of the indicators, and the extension cloud model was introduced to conduct a comprehensive assessment of Shanghai's flood resilience from 2015 to 2023. The results indicate that the flood resilience level in Shanghai has decreased from "moderate" in 2015–2016 to "low" in 2017, before rising to "high" and remaining stable after 2018. In terms of resilience by dimension, Shanghai's flood resilience has gradually evolved from an unbalanced structure to a more balanced state. Specifically, the resilience of the driver dimension remains relatively stable, while the pressure and state dimensions exhibit similar fluctuations. The impact dimension maintains a stable high level, and the response dimension shows significant improvement. Despite the significant achievements made in flood resilience development in recent years, the relevant authorities of Shanghai still need to implement measures to enhance comprehensive flood resilience based on identified weaknesses.